2014
DOI: 10.1016/j.apcbee.2014.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Early Apoptosis Incidence on In Vitro Maturation of Bovine Oocytes

Abstract: Apoptosis in oocyte could be a good marker for oocyte quality and development competency. The study aims to investigate the relation between early apoptosis occurrence in different morphological groups of oocytes, i.e. Group A, B and C, and their developmental potential in terms of meiotic resumption to metaphase II. Annexin-V staining was used to detect early apoptosis in oocytes and Giemsa staining for meiotic resumption. Immature oocytes in Group B and C showed significantly high incidence of early apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Numerous works have shown that the use of CC and oocyte in vitro for genotoxic and cytotoxic evaluation is a valuable and good tool for the rapid and sensitive detection of effect induced by various compound (Anguita et al, 2007;Chung et al, 2007). Furthermore, single cell gel electrophoresis (SCGE), apoptosis, and MTT assay are test used to indicate COC quality (Li et al, 2009;Osman et al, 2013;Aziz et al, 2014). Since few studies have reported the effects of eicosapentaenoic acid (EPA; an n-3 PUFA from fish oil) on bovine oocyte and CC, the aim of this study was to evaluate the influence of EPA supplementation during bovine IVM on CC expansion and oocyte nuclear maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works have shown that the use of CC and oocyte in vitro for genotoxic and cytotoxic evaluation is a valuable and good tool for the rapid and sensitive detection of effect induced by various compound (Anguita et al, 2007;Chung et al, 2007). Furthermore, single cell gel electrophoresis (SCGE), apoptosis, and MTT assay are test used to indicate COC quality (Li et al, 2009;Osman et al, 2013;Aziz et al, 2014). Since few studies have reported the effects of eicosapentaenoic acid (EPA; an n-3 PUFA from fish oil) on bovine oocyte and CC, the aim of this study was to evaluate the influence of EPA supplementation during bovine IVM on CC expansion and oocyte nuclear maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Estos hallazgos coinciden con otros reportes en donde se evidenció que los COC que muestran los signos de atresia temprana como una ligera expansión del cumulo y una ligera granulación del citoplasma tienen mayor o igual potencial de desarrollo que los que se consideran morfológicamente idóneos 9,17,21,28 . Llegando a la conclusión de que existe una relación positiva entre la atresia temprana y la competencia del oocito ya que se ha evidenciado una mejor tasa de maduración y de blastocistos para COC con cúmulo con expansión temprana y ooplasma granular comparado con COC con cúmulo compacto y ooplasma homogéneo 13,32 .…”
Section: Discussionunclassified
“…Aziz y colaboradores reportaron que la apoptosis temprana en CC de oocitos inmaduros bovinos está asociada a competencia oocitaria, ya que no encontraron diferencias en la capacidad de maduración in vitro entre COC con diferentes grados de apoptosis en las células del cumulo determinado por medio de tinción con connexina-V 32 . En cuanto a la capacidad de desarrollo embrionario, Li y colaboradores clasificaron los COC en cuatro grupos según características morfológicas; las tasas de clivaje y de blastocistos fueron superiores para COC con ooplasma granular, comparado con los COC con ooplasma homogéneo 21 .…”
Section: Discussionunclassified
“…Oocytes matured in vivo degenerate if not fertilized. In the ovary, oocytes showing early signs of atresia have high developmental potential (Aziz et al, 2014). Therefore, most oocytes collected from slaughtered animals by slicing will have arisen from atretic follicles.…”
Section: Discussionmentioning
confidence: 99%
“…For gonadotropins to act in vitro, FSHR and LHR genes must be expressed by cumulus cells (Xiao et al, 2014). Gonadotropin-releasing hormone receptors (GnRHRs) are expressed in ovaries (Wei et al, 2013), but their expression in sheep cumulus-oocyte complexes (COCs) has not been described in detail (Aziz et al, 2014;Karami-Shabankareh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%